Difference in kinetics between the distal and proximal parts of the canine parietal cell mass in response to histamine. - Larsson, J O (1983)
Dogs provided with one denervated gastric pouch in the distal part of the corpus fundus and another of equal size in the proximal part, were studied during histamine stimulation. Dose-response curves were determined for acid output and mucosal blood flow, which was measured with the Neutral Red technique. Maximum acid output was significantly higher for the distal (mean 234.0 mumol min-1) than for the proximal pouch (120.0 mumol min-1). ED50 for acid output was significantly higher for the distal (105.0 micrograms kg-1 h-1 of histamine) than for the proximal pouch (57.0 micrograms kg-1 h-1). ED50 for blood flow did not differ significantly between the distal (40.5 micrograms kg-1 h-1) and the proximal pouch (29.0 micrograms kg-1 h-1). For both pouches ED50 for blood flow was significantly lower than that for simultaneous acid output. This indicated that the rise in blood flow precedes that in acid output. Regression analysis showed a significantly higher ratio between maximum mucosal blood flow and maximum acid output for the distal (0.30 ml mumol-1) than for the proximal pouch (0.15 ml mumol-1). The finding that ED50 for acid output in response to histamine was lower for the proximal pouch is contrary to earlier results obtained with pentagastrin, which showed that ED50 was lower for the distal pouch. There is no valid explanation for these differences in ED50 between the pouches, but a difference at receptor level could be hypothesized. The difference in maximum acid output between the two pouches is explained by the known difference between distal and proximal parts in volume fraction of the parietal cells. The possibility that these differences in acid production depend on dissimilarities in mucosal blood flow can be excluded.